FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN NOICED-INDUCED HEARING LOSS (NIHL) PADA NELAYAN KEPULAUAN - Ratna Tanzilla C. Hipi; I Gusti Ayu Trisna Aryani (Jurnal Inovasi Pendidikan dan Sains, 2023)
Indonesia has a nickname as a maritime country. The nickname was given because 2/3 of the Indonesian state is water. The abundant of marine natural resources allow people, especially in coastal areas, to work as fishermen. For most of the day, engine boats used by fishermen to speed fishermen to the fishing site. It is possible that the presence of this ship engine has a negative impact due to the noise caused by it. If this condition continues to occur, it can cause hearing problems in fishermen, namely deafness due to noise or also called Noiced-Induced Hearing Loss (NIHL). Since this disorder is incurable, steps that can be taken are prevention and rehabilitation. As a prevention, it is necessary to know by fishermen what factors can influence the occurrence of hearing loss. Factors affecting the NIHL are classified into internal factors (age) and external factors (noise intensity, length of work and use of Hearing Protective Equipment (HPE)). The purpose of writing this article is expected to be able to introducted of factors related to the occurrence of NIHL in coastal fishermen.